Validity of Augmented Reality-Based Thermodynamics E-LKPD Loaded with Local Wisdom on Evaporation Material for Grade XI Students at Toapaya State Senior High School 1 - Pittanauli; Zaitun; Nevrita; Dody Irawan; Dananjaya (IJGIE (International Journal of Graduate of Islamic Education), 2026)
The use of interactive digital media in physics learning remains limited, and the integration of local wisdom into science education is often overlooked, resulting in less contextual and engaging learning experiences for students. This study aims to develop and determine the validity of an Augmented Reality (AR)-based electronic student worksheet (E-LKPD) integrated with local wisdom on thermodynamics, specifically the evaporation topic for grade XI high school students. This research employed a Research and Development (R&D) approach using the ADDIE model, focusing on the development and evaluation stages. Product validation involved four validators consisting of two physics education lecturers and two experienced high school physics teachers. The validation instrument assessed interface design, interactivity, visual presentation, AR technology stability, media integration, and digital format consistency. Data were analyzed using descriptive quantitative techniques through percentage calculations to determine the validity level. The results indicate that the developed AR-based E-LKPD achieved a highly valid category, exceeding the established feasibility criteria. The integration of AR technology enables interactive visualization of thermodynamics concepts, while the incorporation of local wisdom provides contextual learning experiences for students. Therefore, the developed E-LKPD is feasible as an innovative digital learning medium to support more engaging and meaningful physics learning.